Water Risk Indicator (WaRisk) - Inaliah, Mohd Ali; Norhayati, Mat Husin; Bakhtiar, Alrazi; Noorlin, Mohd Ali; Iliana, Mohd Ali (GBMR, 2018)
Water Risk Indicator (WaRisk) is a computerized system interface entails eight elements: (1) water withdrawal, (2) significance of water withdrawal, (3) water recycled and reused, (4) water risks, (5) facility level water accounting, (6) governance and strategy, (7) compliance, complaints and senses; and (8) targets and initiatives. This study explains the water risk profile for industries after considering the 8-elements. The aims of this paper comprise of: (1) illustrating the WaRisk interface design, explanation and theoretical justification, (2) proposing a suggested tool for water risk indicator specifically for regulators and industries and (3) providing optional ways of activities after identifying the disputes in water management. A sample of 30 companies are employed from public listed companies to originate the proposed interface for this system of water risk indicator. Hence, this paper provides suggestion of interface design for WaRisk system based on the eight indicators.